2016
DOI: 10.2174/1573406412666160201121456
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Phenyliminoindolin-Containing Phenylacetamide Derivatives with the Antidepressant and Anticonvulsant Effects

Abstract: In conclusion, compound 2b produced significant antidepressant-like activity and the mechanism of action may be due to increased 5-HT and NE in the mouse. Compound 2b showed more anticonvulsant effect. Compound 2b could potentially be used as adjuncts of the antidepressants to treat depression in patients with epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Benzeneacetamide was also produced by S. omiyaensis SCH2 and S. pluripotens MUSC137 from mangrove sediments [18,44]. Previous studies reported that benzeneacetamide exhibited significant antibacterial, antidepressant and anticonvulsant effects [51][52]. In addition, natural deferoxamine was detected in the crude extracts of S. malaysiense MUSC 136 T and S. pluripotens MUSC137 isolated from mangrove soil samples [11,44].…”
Section: Discussionmentioning
confidence: 93%
“…Benzeneacetamide was also produced by S. omiyaensis SCH2 and S. pluripotens MUSC137 from mangrove sediments [18,44]. Previous studies reported that benzeneacetamide exhibited significant antibacterial, antidepressant and anticonvulsant effects [51][52]. In addition, natural deferoxamine was detected in the crude extracts of S. malaysiense MUSC 136 T and S. pluripotens MUSC137 isolated from mangrove soil samples [11,44].…”
Section: Discussionmentioning
confidence: 93%
“…( E,E )-2,4-Decadienal exhibited strong paralytic activity on second-stage Meloidogyne incognita, Meloidogyne javanica and Meloidogyne arenaria juveniles (Ntalli et al, 2016 ). Guan et al ( 2016 ) reported benzeneacetamide as an antidepressant-like and anticonvulsant compound. Phenolic compounds were alluded to as potent antimicrobial agents, as are free radical terminators, as they possess hydrogen-donating capability to reduce free radicals (Yogeswari et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The goal of this study was to develop compounds that cure symptoms of depression while also preventing neurodegeneration, thereby con rming the validity of our medicinal design concept. In this report, we used a fusion technique to create effective multi-target ligands (MTDLs) [33][34][35] and combined this approach with previous research ndings [36][37][38][39], as shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%